Is Melatonin the Cornucopia of the 21st Century? - Nadia Ferlazzo; Giulia Andolina; Attilio Cannata; Maria Giovanna Costanzo; Valentina Rizzo; Monica Currò; Riccardo Ientile; Daniela Caccamo (MDPI AG, 2020)
Melatonin, an indoleamine hormone produced and secreted at night by pinealocytes and extra-pineal cells, plays an important role in timing circadian rhythms (24-h internal clock) and regulating the sleep/wake cycle in humans. However, in recent years melatonin has gained much attention mainly because of its demonstrated powerful lipophilic antioxidant and free radical scavenging action. Melatonin has been proven to be twice as active as vitamin E, believed to be the most effective lipophilic antioxidant. Melatonin-induced signal transduction through melatonin receptors promotes the expression of antioxidant enzymes as well as inflammation-related genes. Melatonin also exerts an immunomodulatory action through the stimulation of high-affinity receptors expressed in immunocompetent cells. Here, we reviewed the efficacy, safety and side effects of melatonin supplementation in treating oxidative stress- and/or inflammation-related disorders, such as obesity, cardiovascular diseases, immune disorders, infectious diseases, cancer, neurodegenerative diseases, as well as osteoporosis and infertility.